2005
DOI: 10.1210/en.2005-0587
|View full text |Cite
|
Sign up to set email alerts
|

Permeation of Growth Hormone across the Blood-Brain Barrier

Abstract: Exogenous GH can affect central nervous system function when given peripherally to animals and as a supplemental therapy to humans. This study tested whether GH crosses the blood-brain barrier (BBB) by a specific transport system and found that both mice and rats have small but significant uptake of GH into the brain without a species difference. Determined by multiple-time regression analysis, the blood-to-brain influx transfer constants of 125I-labeled rat GH in mice (0.23+/-0.07 microl/g.min) and rats (0.32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 30 publications
4
85
0
Order By: Relevance
“…Our findings support the results of Pan et al (8) that simple diffusion of GH across the blood-brain barrier (BBB) provides an explanation of the dose-dependent effect of peripheral GH on CNS function. Interestingly, GH release can be stimulated considerably by inhibiting cerebral AChE.…”
supporting
confidence: 92%
“…Our findings support the results of Pan et al (8) that simple diffusion of GH across the blood-brain barrier (BBB) provides an explanation of the dose-dependent effect of peripheral GH on CNS function. Interestingly, GH release can be stimulated considerably by inhibiting cerebral AChE.…”
supporting
confidence: 92%
“…Nevertheless, there are indications that peripheral GH may have direct effects on the brain. First, GH is able to cross the blood-brain barrier (Pan et al 2005). Secondly, the present results demonstrated that AHP cells express the GHR, and that bGH has a direct proliferative effect on these cells in vitro.…”
Section: Direct Effects Of Ghsupporting
confidence: 57%
“…In principle, GH might affect the brain by directly passing through the blood-brain barrier to the brain (Pan et al 2005(Pan et al , Å berg et al 2006) and binding to receptors in the brain (Lobie et al 1993) or by stimulating IGF-I synthesis in the liver which reaches the circulation and the brain via transport through the blood-brain barrier. Indeed, it has been shown that circulating IGF-I elevates hippocampal neurogenesis either by therapy (Å berg et al 2000a(Å berg et al , Trejo et al 2001 or by physical exercise , whereas the role of peripheral GH therapy on adult cell genesis in the brain has, to our knowledge, not been studied at all.…”
Section: Introductionmentioning
confidence: 99%
“…It was further observed that GH-binding in brain tissue decrease as a function of age (257) along with age related decline in GH production as well as cognition and memory (258). However, it is important to note that the GH affecting the central nervous system at any point of time can also have a peripheral source in any other tissue in the body and not necessarily originate in the brain tissues, as GH is known to have a receptor-mediated crossing across the blood-brain-barrier (BBB) (259). In this context, additional sources of GH could be leucocytes (260) and in increasing amounts from ageing splenic lymphocytes(261).…”
Section: Ghr Presence In Brainmentioning
confidence: 99%